Design and development of a high capacity Salvinia Harvester - Hajilal M S (Department of Irrigation and Drainage Engineering, Kelappaji College of Agricultural Engineering and Technology, 1987)
Salvlnla molesta locally known as 'African Payal* ia a noxious floating typo aquatic weed in many parts of the humid tropics. Kerala Agricultural university developed a mechanical device to harvest this menacing weed. An investigation on the performance of the prototype Salvinia Harvester was carried out under various conditions. Prototype ejector E1 with secondary flow straight and primary flow inclined at 900 ejectors E2 and E3 with primary flow straight end secondary flow inclined at 400 and 20° respectively and ejector E4 with secondary flow straight and primary flow inclined at 300 were tested along with circular mouth (M1), adjustable rectangular mouth (M2) and elliptical mouth (M3)• Experiments were also conducted to find out the optimum depth of mouth below the water level.